2004
DOI: 10.2118/04-02-tn2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Dodecyl Benzene Sulfonate on Water-Soluble Hydrophobically Associating Polymer Solutions

Abstract: FIGURE 3: Effect of shear rate on the apparent viscosities of HAP solutions. SDBS concentration = 1.0 × 10 -3 mol/L. FIGURE 4: Effect of shear rate on the apparent viscosities of HAP solutions with or without SDBS. FIGURE 5: Effect of shear rate on the apparent viscosities of HAP solutions with different SDBS concentrations. Cp = 0.20 wt%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…But at high concentration the viscosity decreases due to disruption of associated structures. 131 Similar behavior was observed with sodium dodecyl sulfate. 128 Critical association concentration shifts at lower polymer concentration by increasing the polymer molecular weight.…”
Section: Hydrophobically Modified Associating Polymerssupporting
confidence: 67%
See 1 more Smart Citation
“…But at high concentration the viscosity decreases due to disruption of associated structures. 131 Similar behavior was observed with sodium dodecyl sulfate. 128 Critical association concentration shifts at lower polymer concentration by increasing the polymer molecular weight.…”
Section: Hydrophobically Modified Associating Polymerssupporting
confidence: 67%
“…74 Shear resistance of HMA polymers is also improved when compared to un-modified counterparts. 130 Zhou, et al 131 found that in the semi-dilute region and in the presence of sodium dodecyl benzene sulphonate, HMA polymer showed a shear-thickening behavior. Shear-thickening behavior at low shear rate is due to the transformation from intramolecular association to intermolecular association.…”
Section: Hydrophobically Modified Associating Polymersmentioning
confidence: 99%
“…It is generally believed that the viscosity of HMPAM fluid is made up of non-structure viscosity and structure viscosity. 16 Non-structure viscosity is controlled by the hydrodynamic size of a single polymer molecule, and the structure viscosity is determined by the strength and size of the dynamic physical crosslinking network formed by hydrophobic association. And the network structure is destroyed by the strong action of a high shear rate, leading to decreases in both structure viscosity and non-structure viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrophobically modified HPAM (HMPAM) has been developed by incorporating a small number of hydrophobic branches into the hydrosoluble backbone. , The underlying mechanism is that the nonpolar groups attempt to escape from the polar environment and congregate, resulting in the formation of a spatial network structure. It is generally believed that the viscosity of HMPAM fluid is made up of non-structure viscosity and structure viscosity . Non-structure viscosity is controlled by the hydrodynamic size of a single polymer molecule, and the structure viscosity is determined by the strength and size of the dynamic physical crosslinking network formed by hydrophobic association.…”
Section: Introductionmentioning
confidence: 99%